PENERAPAN METODE SAS BERBANTUAN MEDIA SPIN BACA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN - Muhammad Rivan; Septiyati Purwandari; Agrissto Bintang A.P (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the application of the SAS reading learning method to improve the beginning reading skills of lower grade A students at SD Tumbuh 2 Yogyakarta. The method used in this research is classroom action research. Data collection techniques include observation, testing, and documentation instruments. The research subjects were lower-A class students of SD Tumbuh 2 Yogyakarta, with a total of 16 students. The research data collected was then analyzed using descriptive statistics. The results of the research in the pre-cycle only reached 65.6, which showed that the average score obtained had not reached the Minimum Completion Criteria (KKM) of 75. In cycle I, the average score increased to 70.2, and in cycle II, it increased again to 79.8, which had reached the KKM score. It can be concluded that the SAS method, assisted by spin reading media, can improve students' reading skills.